New perspectives on assessment and understanding of the patient with cranial bone defect: a morphometric and cerebral radiodensity assessment - Oliveira, Arthur Maynart Pereira; De Andrade, Almir Ferreira; Pipek, Leonardo Zumerkorn; Iaccarino, Corrado; Rubiano, Andres M.; Amorim, Robson Luis; Teixeira, Manoel Jacobsen; Paiva, Wellingson Silva (Frontiers in Surgery, 2024)
Background: Skull defects after decompressive craniectomy (DC) cause physiological changes in brain function and patients can have neurologic symptoms after the surgery. The objective of this study is to evaluate whether there are morphometric changes in the cortical surface and radiodensity of brain tissue in patients undergoing cranioplasty and whether those variables are correlated with neurological prognosis. Methods: This is a prospective cohort with 30 patients who were submitted to cranioplasty and followed for 6 months. Patients underwent simple head CT before and after cranioplasty for morphometric and cerebral radiodensity assessment. A complete neurological exam with Mini-Mental State Examination (MMSE), modified Ranking Scale, and the Barthel Index was performed to assess neurological prognosis. Results: There was an improvement in all symptoms of the Trephined Syndromesyndrome of the trephined, specifically for headache (p=0.004) and intolerance changing head position (p=0.016). Muscle strength contralateral to bone defect side also improved (p=0.02). Midline shift of intracranial structures decreased after surgery (p=0.004). The Anterior Distance Difference (ADif) and Posterior Distance Difference (PDif) were used to assess morphometric changes and varied significantly after surgery. PDif was weakly correlated with MMSE (p = 0.03; r = -0.4) and Barthel index (p = 0.035; r = -0.39). The ratio between the radiodensities of gray matter and white matter (GWR) was used to assess cerebral radiodensity and was also correlated with MMSE (p = 0.041, r = -0.37). Conclusion: Morphological anatomy and radiodensity of the cerebral cortex can be used as a tool to assess neurological prognosis after DC.